Paget's disease of the breast in a male with lymphomatoid papulosis: a case report - Fouad Dina (Journal of Medical Case Reports, 2011)
Abstract Introduction Paget's disease is an eczematous skin change of the nipple that is usually associated with an underlying breast malignancy. Male breast cancer represents only 1-3% of all breast malignancies and Paget's disease remains very rare. Case presentation We present the case of a 67-year-old Caucasian man with lymphomatoid papulosis who was diagnosed with Paget's disease of the nipple and who was treated successfully with surgery alone. We discuss the presentation, investigations, management and pathogenesis of Paget's disease of the nipple. Conclusion The case highlights the need to be vigilant when new skin lesions arise in the context of an underlying chronic skin disorder.